The effect of job appraisal and job training on employee performance at PT. Bank Sulselbar Luwu - Adil, Adil; Sapar, Sapar; Jasman, Jumawan (Goodwood Publishing, 2023)
Purpose: This study aimed to determine the effect of job appraisal and job training on the performance of employees of PT. Bank SulSelBar Luwu. Research Methodology: This study used a quantitative research with a descriptive approach. The population in this study comprised all employees working at PT. Bank SulSelBar Luwu. The number of samples in this study was 35. The data analysis technique used was descriptive statistical tests, classical assumption tests, and multiple regression analysis. Results: The results of this study show that: 1. Job appraisal positively and significantly affects employee performance at PT. Bank SulSelBar Luwu, 2. Job training has a positive and significant effect on employee performance at PT. Bank SulSelBar Luwu. 3. The results of the F-test indicate that job appraisal and training simultaneously (together) have a positive and significant effect on employee performance PT. Bank SulSelBar Luwu. Conclusions: This study confirms that both job appraisal and job training are essential determinants of employee performance. Together, these factors contribute significantly to organizational outcomes by improving employees’ skills, awareness of strengths and weaknesses, and overall productivity. Limitations: The study is limited by a small sample size of 35 employees and only two variables, reducing generalizability and scope. Contribution: This research shows that job appraisal and training have a contribution or influence on employee performance variables by 61.90%, while the remaining 38.10% is influenced by other variables not examined in this study.